Forest tenure reform implementation in Uganda: Current challenges and future opportunities - Nsita, S.A.; Nakangu, B.; Banana, A.Y.; Mshale, B.; Mwangi, E.; Ojwang, D. (2020)
This study was carried out in the districts of Kakumiro, Kibaale, Masindi, and Lamwo in Uganda. It focused on district-level government officials involved in the implementation of forest tenure reform in Uganda, but people at the national level who were familiar with forestry and land matters were also interviewed. The study highlighted key challenges and opportunities for future improvements. Analysis of responses shows that: